Role of Macrophage Polarization in Acute Respiratory Distress Syndrome - Priyanka Mishra; Nikhil Pandey; Ratna Pandey; Yamini B Tripathi (MDPI AG, 2021)
Acute Respiratory Distress Syndrome is a familiar and destructive clinical condition characterized by progressive, swift and impaired pulmonary state. It leads to mortality if not managed in a timely manner. Recently the role of imbalanced macrophage polarization has been reported in ARDS. Macrophages are known for their heterogeneity and plasticity. Under different microenvironmental stimuli, they (M0) can switch between classically activated macrophage (M1) and alternatively activated (M2) states. This switch is regulated by several signaling pathways and epigenetic changes. In this review, the importance of macrophage M1 and M2 has been discussed in the arena of ARDS citing the phase-wise impact of macrophage polarization. This will provide a further understanding of the molecular mechanism involved in ARDS and will help in developing novel therapeutic targets. Various biomarkers that are currently used concerning this pathophysiological feature have also been summarized.